A gap analysis modeling framework to prioritize collecting for ex situ conservation of crop landraces - Ramírez Villegas, Julián Armando; Khoury, Colin K.; Achicanoy Estrella, Harold Armando; Mendez Alzate, Andres Camilo; Sosa, Chrystian C.; Debouck, Daniel G.; Kehel, Zakaria; Guarino, Luigi (2021)
Aim: The conservation and effective use of crop genetic diversity is crucial to overcome challenges related to human nutrition and agricultural sustainability. Farmers’ traditional varieties (“landraces”) are major sources of genetic variation. The degree of representation of crop landrace diversity in ex situ conservation is poorly understood, partly due to a lack of methods that can negotiate both the anthropogenic and environmental determinants of their geographic distributions. Here we describe a novel spatial modeling and ex situ conservation gap analysis modeling framework for crop landraces, using common bean (Phaseolus vulgaris L.) as a case study.